PROTECTION OF FREEDOM OF EXPRESSION THROUGH INTERNET MEDIA FROM A HUMAN RIGHTS PERSPECTIVE - Fauzi, Muhamad Andi; Marwiyah, Siti (Kultura: Jurnal Ilmu Hukum, Sosial, dan Humaniora, 2024)
This research is motivated by the basic rights of human rights (HAM), namely the right to freedom of opinion which needs to be analyzed how the protection of freedom of opinion is regulated in the ITE Law. And what is the form of the obligation of the State of Indonesia in protecting the right to freedom of expression on social media. This type of research uses a normative juridical research type using a statutory research approach and a case approach and using primary and secondary legal materials obtained from literature study consisting of primary and secondary law. The results of writing this thesis can be concluded that article 27 paragraph 3 UU ITE only contains obligations that must be fulfilled by social media users and tends to be restrictive because it does not clearly include the rights possessed in using social media, bearing in mind that rights also cause an obligation to respect and respect the rights of others, then the implementation of these rights can be limited through article 28J paragraph 2 of the 1945 Constitution, the State has an obligation to protect freedom of opinion on social media which is regulated constitutionally in the 1945 Constitution, Law no. 39 of 1999, Law no. 12 of 2005. In the form of protecting, respecting and fulfilling human rights (HAM).